Abscess removal in a desert horned viper (Cerastes cerastes) - Puveanthan Nagappan Govendan; Michael Nadhor Nainggolan; . Erika; Slamet Raharjo (School of Veterinary Medicine and Biomedical Sciences, Bogor Agricultural University, 2020)
Venomous snakes are widely kept in captive as collections by private reptile keepers. A 7 years old male desert horned viper (Cerastes cerastes) was presented with a lump on the caudal part of the body. Proper physical restraining method using snake hook and transparent tubes was performed for clinical examination and radiography. Two radiography views revealed radiopaque in both lateral and dorsal recumbence. Differential diagnosis was tumor growth and abscess. Surgical intervention was indicated and performed with the viper induced with injectable anesthesia and maintained with gas anesthesia. Surgical correction with manually removing the abscess was performed. The NSAID, broad spectrum antibiotic, topical antibiotic and fluid therapy were performed post-surgery. Six weeks post-surgery the suture material was removed and wound was dry and healed well.